2016
DOI: 10.1021/acsnano.5b06465
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Acoustic Phonons in Colloidal Semiconductor Nanocrystal Superlattices

Abstract: The phonon properties of films fabricated from colloidal semiconductor nanocrystals play a major role in thermal conductance and electron scattering, which govern the principles for building colloidal-based electronics and optics including thermoelectric devices with a high ZT factor. The key point in understanding the phonon properties is to obtain the strength of the elastic bonds formed by organic ligands connecting the individual nanocrystallites. In the case of very weak bonding, the ligands become the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 54 publications
2
53
0
Order By: Relevance
“…Penciu et al 30 and Kuok et al 31 first applied BLS to measure the eigenfrequencies of giant micelles and silica NPs of submicrometer size. For NPs with a diameter <100 nm, Raman scattering and pump probe techniques could be applied, however, fewer modes are resolved 32 36 . Recently, particle vibration spectroscopy by means of BLS has been advanced to measure particle mechanical eigenfrequencies to determine the elastic properties of polymer NPs 37 39 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penciu et al 30 and Kuok et al 31 first applied BLS to measure the eigenfrequencies of giant micelles and silica NPs of submicrometer size. For NPs with a diameter <100 nm, Raman scattering and pump probe techniques could be applied, however, fewer modes are resolved 32 36 . Recently, particle vibration spectroscopy by means of BLS has been advanced to measure particle mechanical eigenfrequencies to determine the elastic properties of polymer NPs 37 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on this approach, we use BLS to measure the T g of PS NPs and to specify the mobile layer driven NP interactions. The experiments allow us to observe the vibrational modes of cluster of polymer NPs whose frequencies changed depending on the interactions among the NPs 35 , 36 , 45 47 . The T g of the PS NPs is measured by the temperature dependence of the vibrational modes.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Whereas this provides ample possibilities to combine different nanocrystals in a single, ordered crystal, only few studies have shown such an approach to result in metamaterials with new or enhanced properties. [14][15][16] For one thing, this is due to the use of nanocrystal building blocks capped by long, organic ligands, which inevitably leads to electrically insulating nanocrystal solids. Therefore, opto-electronic devices such as transistors, [17][18][19] solar cells [20][21][22][23] or photodetectors, [24][25][26] are based on disordered QD solids, where the interparticle distance is usually decreased by exchanging the long organic ligands with shorter organic or inor-ganic moieties.…”
mentioning
confidence: 99%
“…[27][28][29][30][31] Although this makes for QD devices with ever increasing performance, carrier mobilities remain well below 10 cm 2 V −1 s −1 and the approach leaves no room for any symmetry-induced collective effects. 15,32,33 Recently, it was shown that PbSe QDs can be organized into ordered two dimensional (2D) superlattices in which all QDs are epitaxially connected to their nearest neighbors. [34][35][36][37][38] As demonstrated by Evers et al, the strong electronic interdot coupling in such epitaxially connected 2D quantum-dot superlattices -epitaxial superlattices in short -results in carrier mobilities of up to 260 cm 2 V −1 s −1 as deduced from THz conductivity measurements.…”
mentioning
confidence: 99%
“…The state-of-the-art methods for nanomechanic measurements are based on deformation, 15,16 or on acoustic wave propagation. 17,18 Both methods pose limitations: the former is destructive, while the latter requires a complex sample preparation. Both assume linear stress-strain relationship, 19 and cannot resolve the direction-dependent mechanical behaviors.…”
mentioning
confidence: 99%